Estratégias de manejo de Meloidogyne incognita raça 1 em cafeeiro conilon - Zinger, Fernando Domingo (2015)
Commercial exploitation of the crop is one of the most important activities of the global agricultural sector, Brazil and Espírito Santo, according to the Brazilian State in coffee production and the first in conilon coffee production. One of the main phy